ANALYSIS OF PROFITABILITY, WORKING CAPITAL, INVENTORY BEFORE AND AFTER THE COVID-19 PANDEMIC: EMPIRICAL STUDY FROM THE PHARMACEUTICAL INDUSTRY - Irdha Yusra; Rizka Hadya; Saiful Anwar (Jurnal Apresiasi Ekonomi, 2023)
This study intends to investigate the impact of working capital turnover and inventory turnover on profitability, as well as to demonstrate the differences in working capital turnover and inventory turnover before and after Covid-19. The study was carried out at pharmaceutical sub-sector companies that are listed on the Indonesia Stock Exchange. The causality effect is estimated using panel data regression estimation in the EViews 10 program, while the comparative objective is analyzed using various tests in the SPSS 26 program. The research variable causality test results show that partial working capital turnover affects profitability while inventory turnover does not. Working capital turnover and inventory turnover, on the other hand, have a positive and significant effect on the profitability of pharmaceutical sub-sector companies. Furthermore, there was no significant difference in working capital turnover and inventory turnover before and after the Covid-19 pandemic, according to the comparative test results.